Coproduction and mental health service provision: a protocol for a scoping review - Michael John Norton (BMJ Open)
Introduction Since the turn of the millennium, recovery has become mainstream in mental health services across much of the Western world. Resulting from this, many jurisdictions, including Ireland, have created frameworks and policies to support its integration into traditionally, statutory mental health services. Coproduction is a cornerstone of recovery. However, there is confusion about what the term means, along with queries surrounding its implementation. Consequently, studies have identified that coproduction compliments recovery in several ways. This has been found to have a positive impact on a service user’s ongoing recovery journey. However, no synthesis has yet been undertaken into coproduction within mental health service provision. As such, this protocol aimed to provide information on a scoping review to examine the evidence base for coproduction within mental health service provision.Methods and analysis A Preferred Reporting Items for Systematic Reviews and Meta-Analysis compliant scoping review is proposed, based on Arksey and O’Malley’s framework. This framework documents a five-stage approach to conducting scoping reviews. Search terms are stated and a variety of databases (CINAHL, Jstor, Ovid SP, PsycINFO, PsycTEST, PubMed, RCNi, Science Direct, Web of Science and Wiley Online Library) and repositories (Cochrane Online Library, ETHos, nz.research.org.nz, ProQuest, National ETD Portal, Google, Google Scholar and ResearchGate) will be examined for papers based on inclusion/exclusion criteria. The search range is from 1 January 1970 to 31 December 2021.Ethics and dissemination This paper is a protocol which requires no ethical approval. Information relating to the review is stored with OSF Registries, where it is freely available. The protocol details were updated in February and again in May 2022. The resulting scoping review will be distributed through peer-reviewed publications.